2007
DOI: 10.1016/j.neuroscience.2007.07.067
|View full text |Cite
|
Sign up to set email alerts
|

A chronic histopathological and electrophysiological analysis of a rodent hypoxic–ischemic brain injury model and its use as a model of epilepsy

Abstract: Ischemic brain injury is one of the leading causes of epilepsy in the elderly, and there are currently no adult rodent models of global ischemia, unilateral hemispheric ischemia, or focal ischemia that report the occurrence of spontaneous motor seizures following ischemic brain injury. The rodent hypoxic-ischemic (H-I) model of brain injury in adult rats is a model of unilateral hemispheric ischemic injury. Recent studies have shown that an H-I injury in perinatal rats causes hippocampal mossy fiber sprouting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 86 publications
1
16
0
Order By: Relevance
“…A detailed histological study of the brains of rats 6 months following HI treatment revealed features such as porencephalic cysts and cortical microgyri which are similar to findings following perinatal HI in humans (Kadam and Dudek, 2007;Marin-Padilla, 2000;Villani et al, 2003). Interestingly, mossy fiber sprouting into the molecular layer of the dentate gyrus has been documented as well (Kadam and Dudek, 2007;Williams et al, 2004;Williams and Dudek, 2007). This type of anatomic plasticity is of particular interest because it is known to occur in human temporal lobe epilepsy and models of that disorder, and furthermore it has been suggested to possibly play are role in epileptogenesis Frotscher and Zimmer, 1983;Tauck and Nadler, 1985).…”
Section: Histology and Pathologymentioning
confidence: 55%
See 2 more Smart Citations
“…A detailed histological study of the brains of rats 6 months following HI treatment revealed features such as porencephalic cysts and cortical microgyri which are similar to findings following perinatal HI in humans (Kadam and Dudek, 2007;Marin-Padilla, 2000;Villani et al, 2003). Interestingly, mossy fiber sprouting into the molecular layer of the dentate gyrus has been documented as well (Kadam and Dudek, 2007;Williams et al, 2004;Williams and Dudek, 2007). This type of anatomic plasticity is of particular interest because it is known to occur in human temporal lobe epilepsy and models of that disorder, and furthermore it has been suggested to possibly play are role in epileptogenesis Frotscher and Zimmer, 1983;Tauck and Nadler, 1985).…”
Section: Histology and Pathologymentioning
confidence: 55%
“…Moreover, release of caged glutamate in the granule layer resulted in repetitive EPSCs in granule cells in patch clamp experiments. These findings are suggestive of excitatory feedback in the HI treated animals (Williams and Dudek, 2007). Although these experiments were carried out in rats treated at P30 they are possibly quite relevant to the neonatal HI model in that rats treated at P7 also undergo mossy fiber sprouting (Kadam and Dudek, 2007;Williams et al, 2004).…”
Section: Changes In Network Excitabilitymentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, excitatory drive to surviving hilar GABAergic interneurons after CCI may be enhanced by convergent input from both pyramidal and granule cells resulting in network destabilization (Hunt et al, 2011). The presence of aberrant mossy fiber sprouting in the IML of the hippocampus is typically considered as a marker for temporal lobe epilepsy and as one of several abnormal excitatory networks that may underlie seizure generation (Gorter et al, 2001;Williams and Dudek, 2007).…”
Section: Brain Pathologymentioning
confidence: 99%
“…To this end, new syndrome-specific models have been developed based on etiologically realistic epileptogenic insults such as viral encephalitis, stroke, febrile seizures, perinatal hypoxia and head trauma (D’Ambrosio et al, 2004; Dubé et al, 2010; Kelly et al, 2001; Rakhade et al, 2011; Williams and Dudek, 2007). These models have the advantages that: 1) they feature chronic spontaneous recurrent seizures (CSRSs), which are the hallmark of epilepsy, 2) they include focal non-convulsive CSRSs, which are known to be difficult to treat with current ASDs, 3) the realism of the initiating injury ensures that mechanisms that operate in the corresponding patient populations are recruited, and 4) the patient populations best suited for clinical tests of treatments discovered using these models are readily identifiable.…”
Section: Introductionmentioning
confidence: 99%